Tác động của chuyển đổi số và mức độ sử dụng kế toán quản trị đến hiệu quả bền vững: Vai trò điều tiết của lãnh đạo chuyển đổi tại các doanh nghiệp Việt Nam - Nguyễn Trọng, Phương; Quảng Thị , Phương; Hoàng Cẩm, Trang; Nguyễn Phong, Nguyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the structural relationships between digital transformation, management accounting system use, and sustainable performance, while evaluating the moderating influence of transformational leadership within the context of Vietnamese enterprises. Utilizing a partial least squares - structural equation modeling analysis of 326 valid survey responses, the findings reveal that digital transformation exerts a significant positive impact on both management accounting system use and sustainable performance. This research addresses a critical theoretical gap by elucidating the transmission mechanism through which digital infrastructure is converted into sustainable value via management accounting system use, which serves as a substantial partial mediator. Furthermore, the results confirm that transformational leadership significantly strengthens the positive effect of management accounting system use on sustainable performance. By integrating the resource-based view and the information systems success model, the study suggests that firms should prioritize real-time data standardization and cultivate digital leadership capabilities aligned with a triple bottom line orientation to optimize sustainable net benefits.